Densely PEGylated Polybenzofulvene Brushes for Potential Applications in Drug Encapsulation - Marco Paolino; Giorgio Grisci; Federica Castriconi; Annalisa Reale; Germano Giuliani; Alessandro Donati; Claudia Bonechi; Gianluca Giorgi; Raniero Mendichi; Daniele Piovani; Antonella Caterina Boccia; Maurizio Canetti; et al. (MDPI AG, 2018)
The technique of grafting side chains onto a linear polymeric backbone is commonly used to confer to the new polymeric material with desired properties, such as tunable solubility, ionic charge, biocompatibility, or specific interactions with biological systems. In this paper, two new polybenzofulvene backbones were assembled by spontaneous polymerization of the appropriate benzofulvene monomers (4,6-PO-BF3k and 4’,6-PO-BF3k) bearing two clickable propargyloxy groups in different positions of the 3-phenylindene scaffold. Poly-4,6-PO-BF3k and poly-4’,6-PO-BF3k were grafted with monomethyl oligo(ethylene glycol) (MOEG) to prepare two new polybenzofulvene brushes (i.e., poly-4,6-MOEG-9-TM-BF3k and poly-4’,6-MOEG-9-TM-BF3k) by means of a “grafting onto„ approach, that were characterized from the point of view of their macromolecular features, aggregation liability, and in a preliminary evaluation of biocompatibility. The obtained results make these PEGylated polybenzofulvene brushes (PPBFB) derivatives potentially useful as nanocarriers for nanoencapsulation and delivery of drug molecules.